2008
DOI: 10.1128/jvi.00124-08
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Follicular Dendritic Cell Reservoir of Human Immunodeficiency Virus Type 1

Abstract: Throughout the natural course of human immunodeficiency virus (HIV) infection, follicular dendritic cells (FDCs) trap and retain large quantities of particle-associated HIV RNA in the follicles of secondary lymphoid tissue. We have previously found that murine FDCs in vivo could maintain trapped virus particles in an infectious state for at least 9 months. Here we sought to determine whether human FDCs serve as an HIV reservoir, based on the criteria that virus therein must be replication competent, geneticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
115
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(122 citation statements)
references
References 56 publications
5
115
0
2
Order By: Relevance
“…Ce concept de réservoir a pris toute son importance peu de temps après l'introduction de la multithérapie active en 1996, quand plusieurs auteurs ont démontré la persistance du virus, qui s'était intégré de manière latente dans des cellules T CD4 + , chez des patients traités par au moins trois molécules antirétrovirales 2 (ce que l'on désigne par le terme HAART pour highly active anti retroviral therapy), ruinant alors les espoirs fondés sur l'éradication totale du virus [7][8][9]. Depuis lors, il a été montré que d'autres types cellulaires que les lymphocytes T CD4 + pouvaient servir de réservoir du VIH-1 [32] : c'est le cas des cellules de la lignée monocyte-macrophage [10] dont les cellules microgliales qui sont les macrophages résidants du système nerveux central [11], et des cellules dendritiques [12].…”
Section: Le Maintien De La Latence Viraleunclassified
“…Ce concept de réservoir a pris toute son importance peu de temps après l'introduction de la multithérapie active en 1996, quand plusieurs auteurs ont démontré la persistance du virus, qui s'était intégré de manière latente dans des cellules T CD4 + , chez des patients traités par au moins trois molécules antirétrovirales 2 (ce que l'on désigne par le terme HAART pour highly active anti retroviral therapy), ruinant alors les espoirs fondés sur l'éradication totale du virus [7][8][9]. Depuis lors, il a été montré que d'autres types cellulaires que les lymphocytes T CD4 + pouvaient servir de réservoir du VIH-1 [32] : c'est le cas des cellules de la lignée monocyte-macrophage [10] dont les cellules microgliales qui sont les macrophages résidants du système nerveux central [11], et des cellules dendritiques [12].…”
Section: Le Maintien De La Latence Viraleunclassified
“…This more prolonged third decay phase has been estimated to have a half-life of around six months [43,65], although a half-life of 30 months during HAART was estimated in another study [66], and mathematical modelling studies have shown HIV:FDC interactions to persist for years, despite effective HAART [67]. Through phylogenetic analysis of the HIV that interacts with FDCs isolated from 2 out of 4 patients, the virus present was similar to the virus isolated 22 months earlier, which suggests long-term FDC sequestration of replication-competent HIV [68]. However, other studies have shown DC-SIGN being unable to protect against virion degradation, since loss of HIV infectivity was reported over a course of hours [69].…”
Section: Follicular Dendritic Cellsmentioning
confidence: 99%
“…These include cells in the central nervous system (CNS) [12] and male urogenital tract [13], as well as macrophages [14] and follicular dendritic cells [15]. There is also evidence that low levels of ongoing viral replication might continue even in patients receiving HAART who are clinically aviraemic and for whom plasma HIV-1 RNA levels are below the limit of detection of standard assays.…”
Section: Hiv Type-1 Latency: Targeted Induction Of Proviral Reservoirsmentioning
confidence: 99%
“…Additional reservoirs have been identified, including those in macrophages and follicular dendritic cells [14,15]. Strategies sufficient to activate latent virus in CD4 + T-cells might not be applicable to other cellular reservoirs, or pharmacological issues might limit their efficacy.…”
Section: Memory Cd4mentioning
confidence: 99%